Product Diversification and E-Commerce Optimization as an Effort to Escalate Sales and UMKM Competitiveness of Bidai Handicraft in Singkawang City - Mertika, Mertika; Wahyuni, Rika; Nirawati, Resy; Kariadi, Dodik; Suwanto, Insan; Marhayani, Dina Anika; Buyung, Buyung; Rosmaiyadi, Rosmaiyadi (International Journal of Public Devotion, 2024)
The problems faced by partners are related to the implementation mechanism or product diversification process, related to the knowledge and skills of Kastaman Bidai craftsmen's creativity is still low. An effort is needed to overcome the problems faced by Kastaman Bidai UMKM partners.  STKIP Singkawang through the Product Diversification Program and E-Commerce optimization as an effort to escalate sales and business competitiveness to Kastaman Bidai UMKM. Implementation method by providing training and assistance in the form of preparing digital financial reports, diversifying bidai products, marketing and digital advertising of bidai products. The results obtained are that the Program can be implemented very well, 2. The understanding and skills of Kastaman Bidai UMKM Partners regarding the preparation of digital financial reports, diversification of bidai products, marketing and digital advertising of bidai products are very good and Kastaman Bidai UMKM Partners can produce Bidai derivative products